APLIKASI AKAD MURABAHAH PRODUK PEMBIAYAAN SYARIAH KENDARAAN BERMOTOR PADA PT. MANDIRI UTAMA FINANCE (MUF) CABANG JEMBER BERDASARKAN FATWA DSN-MUI NO. 04/DSN-MUI/IV/2000 - Syafi’i, Muhammad; Shodiqin, Dimas Herliadis (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
Community economic growth can be seen from the level of community economic mobility. Economic mobility will move supported by adequate means of transportation. The latest data states that the number of motorized vehicles in Indonesia is 141,992,573 units, both two-wheeled and more. The development of the number of motorized vehicles is influenced by increasing purchasing power and support from financial institutions in procuring motorized vehicles. One of the financial institutions that provides financing products for motor vehicle ownership is PT. Mandiri Utama Finance (MUF), which has a branch office in the city of Jember. One of the products is the Murabahah contract. Purchase of motorized vehicles in installments according to Sharia principles. The aim of the research is to describe the application of Murabahah products at PT. Mandiri Utama Finance (MUF) Jember branch in accordance with and based on DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000. Research method, type of qualitative research with a qualitative descriptive approach. The data collection method uses interview, observation and documentation methods, then the results of data collection are analyzed using data reduction methods, data presentation and drawing conclusions. The data validity method uses the method of persistence and consistency of researchers in the field. The results of this research explain that the murabahah contract product at PT. Mandiri Utama Finance (MUF) Jember branch is running in accordance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, but weak in Sharia marketing methods and energy. Keywords: Murabahah contract application, DSN-MUI Fatwa, PT. Mandiri Utama Finance